Using difference modelling and computational fluid dynamics to investigate the evolution of complex, tidally influenced shipwreck sites. (15th February 2022) - Majcher, Jan; Quinn, Rory; Smyth, Thomas; Plets, Ruth; McGonigle, Chris; Westley, Kieran; Sacchetti, Fabio; Coughlan, Mark
Abstract: The large number of historic metal-hulled shipwrecks on the seabed is a major consideration for the marine environment, heritage management and spatial planning. Their stability is driven by linked hydro- and sediment-dynamics, which in turn influence chemical corrosion and biological encrustation. The dynamism at underwater sites is frequently expressed in elaborate patterns of depositional and erosional features developed due to seabed scour. These settings are complex, due to the variable morphologies of the wrecks, and diverse types of seabed geology and geomorphology. Not only are the flow patterns and geomorphic changes at shipwreck sites not fully understood, but how these influence the wreck structures remains under-researched. Here we combine high-resolution multibeam echosounder, ocean current and sediment data with 3D Computational Fluid Dynamics (CFD) to investigate interrelations between hydro- and sediment-dynamics and the deterioration of two complex, fully submerged tidally-influenced shipwrecks. Intricate patterns of wake and horseshoe vortices are observed, and modelled wall shear stresses predict geomorphic changes recorded in 4-year and one-week interval difference models. Moreover, substantial damage is detected on the wrecks, correlated with areas of elevated wall shear stress and pressure in CFD simulations. The combined approach aids site management and provides analogies for offshore engineering. Highlights: The sheer number of metal shipwrecks on the seabed creates perplexing management challenges. Their structures significantly influence, and are influenced by, the local hydro- and sediment-dynamic settings. Computational fluid dynamics and difference modelling using bathymetric data provide new insights into wreck deterioration. Intricate patterns of simulated flows and wall shear stresses correspond to the areas of sediment erosion and deposition.